"Lez be honest": Gender expression impacts workplace disclosure decisions. Issue 2 (3rd April 2019) - Hamilton, Kelly M.; Park, Lauren S.; Carsey, Timothy A.; Martinez, Larry R.
Abstract: We introduce a theoretical framework of lesbian disclosure of sexual orientation in workplace contexts. Existing empirical research suggests (1) that disclosing one's sexual orientation results in positive, negative, and neutral workplace outcomes; and (2) that scholarship focused specifically on lesbian disclosure in workplace contexts is relatively limited. We extend this literature by introducing new theory that suggests that reactions to disclosure of lesbian identities will vary as a function of self-presentation. Specifically, we suggest that the extent of stereotypical gender expression (embodying stereotypically masculine vs. feminine traits or behaviors) will impact both the decision to disclose and the outcomes of disclosure in workplace contexts. We describe a conceptual model that includes intrapersonal, interpersonal, organizational, and societal considerations related to lesbian disclosure and present eight specific research propositions to advance this literature.